2021
DOI: 10.1108/jabes-08-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

Hedging, managerial ownership and firm value

Abstract: PurposeThis study investigates the impact of derivatives as risk management strategy on the value of Malaysian firms. This study also examines the interaction effect between derivatives and managerial ownership on firm value.Design/methodology/approachThe study examines 200 nonfinancial firms engaged in derivatives for the period 2012–2017 using the generalized method of moments (GMM) to establish the influence of derivatives and managerial ownership on firm value. The study refers to two related theories (hed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
(149 reference statements)
1
7
0
4
Order By: Relevance
“…This study obtained results that are in line with Feng et al (2020) and Suhadak et al (2020) who found that increasing institutional ownership will reduce agency costs arising from agency conflicts because of the separation of management and ownership. From the results of the analysis, it can be proven that the higher the institutional ownership, which means the higher the institutional investors, the more effective the supervision of managers in the use of debt so that opportunistic behavior can be prevented and the interests between managers and shareholders can be aligned (Zamzamir@Zamzamin et al, 2021). This alignment of interests is followed by an increase in the performance of managers because managers are encouraged to fulfill the interests of shareholders (Mahrani & Soewarno, 2018).…”
Section: Moderation Effect Of Institutional Ownership On the Relation...mentioning
confidence: 98%
“…This study obtained results that are in line with Feng et al (2020) and Suhadak et al (2020) who found that increasing institutional ownership will reduce agency costs arising from agency conflicts because of the separation of management and ownership. From the results of the analysis, it can be proven that the higher the institutional ownership, which means the higher the institutional investors, the more effective the supervision of managers in the use of debt so that opportunistic behavior can be prevented and the interests between managers and shareholders can be aligned (Zamzamir@Zamzamin et al, 2021). This alignment of interests is followed by an increase in the performance of managers because managers are encouraged to fulfill the interests of shareholders (Mahrani & Soewarno, 2018).…”
Section: Moderation Effect Of Institutional Ownership On the Relation...mentioning
confidence: 98%
“…Maximize firm value with external funding called leverage (Zamzamir, Haron, and Othman, 2021). Leverage can be proxy with Debt to Equity Ratio (DER), which is a measure to show how many companies are financed (Sukma, Nurtina and MH Nainggolan, 2022).…”
Section: Independent Variable Leverage (X1)mentioning
confidence: 99%
“…Managers could manage to maximize firm value with external funds called leverage (Zamzamir, Haron, and Othman, 2021). It was explained that if the level of a company's leverage ratio is high, it means that the company will withhold the company's operating profit so that it can be used to pay off the company's debts.…”
Section: Introductionmentioning
confidence: 99%
“…When a firm decides on its financial assistance methods either using debt or equity or even a combination of both, firms need to take into account several influencing factors in their capital structure. Capital structure is undoubtedly a crucial element in the operation of a firm which aims primarily at reducing cost of capital as well as achieving maximum firm value (Khaw, 2019;Musallam, 2020) and serve as strong pillars that lend competitive advantage to a firm (Kumar et al, 2017;Zamzamin et al, 2021). Recognized as an important subject matter of discussion because of its significant influence over firm value, it has been a highly debated issue among researchers and policymakers in the finance literature, covering the developed as well as the emerging markets over the decades worldwide (Haron, 2016;Kumar et al, 2017;Ramli et al, 2019;Khaw, 2019).…”
Section: Introductionmentioning
confidence: 99%